Sociology : a brief introduction - Thio, Alex (New York : Harper Collins College Publishers, 1994)
Social Science
Keywords: Sociology; Culture; Social structure; Socialization; Social stratification; Race; Ethnicity; Gender; Religion; Politics; Economy; Education; Population; Ecology; Urbanization; Social behavior; Social change